The use of sensors and GIS in studying the dynamics of vegetation coverage in the Algerian steppes - Hadjadj, Nadjet; Hadeid, Mohamed (Technium Social Sciences Journal, 2022)
The present research aims to study the dynamics of vegetation coverage in the Algerian steppe region. In order to calculate the vegetation coverage index (Ndvi) for three distinct time periods between 1984 and 2022, we used satellite imagery analysis and remote sensing and geographic information systems (GIS). Remote sensing and GIS are two of the most significant digital tools for gathering, analyzing, and studying the geographic field in all of its dimensions. They also help track changes that are occurring in that field. The changes that were known to the vegetation cover in the study area, and we also employed the Union icon in the Arcmap program in order to know the most important changes that occurred.